ASABI App: Mobile learning media for learning procedure texts in the seventh grade of junior high school - Chintiya Dewi, Fadilla; Samhati, Siti; Sumarti, Sumarti; Rusminto, Nurlaksana Eko (Universitas Negeri Yogyakarta, 2024)
The purpose of this study was to describe the use and benefits of using the ASABI application in learning procedure texts in junior high school. The research was developmental research using the Hannafin and Peck model. The data was taken from Junior High School 12 of Bandar Lampung. The results of this study indicated that 89% of respondents agree that the ASABI application provides benefits in learning procedure text. The ASABI application can be used in learning procedure texts in junior high school. There was an increase in learning motivation in students themselves. The advantages obtained from the ASABI application include 1) a more attractive appearance and ability to increase enthusiasm for learning, 2) easy to use, 3) the material is easier to understand, 4) more practical and economical, and 5) equipped with evaluation questions accompanied by feedback. The use of the ASABI application in procedural text learning was not only providing benefits for students but also for the educator.